Um Jogo que estimula o aprendizado da criptografia RSA - Escobar, Karina Marchetti Bonno (2019)
In this work, we present the main mathematical results that justify the operation of RSA encryption and its security, such as Fermat’s small theorem, Diophantine equations and Chinese remainder theorem. We also present the importance of games, especially RPG textit Maker, in math classes. In order to apply RSA cryptogria, an electronic RPG (Role Playing Game) game was created.